Analysis Of The Implementation Of The First 1,000 Days Of Life (1,000 HPK) Specific Nutrition Intervention Program For Stunting Management At Sarwodadi Community Health Center, Pemalang Regency, In 2025 - Adinda Ismail Putri; Yuniarti Yuniarti; Ristiawati Ristiawati (CV. AFDIFAL MAJU BERKAH, 2026)
Stunting remains a significant public health problem in Indonesia. The Sarwodadi Community Health Center is one of the areas with a relatively high prevalence of stunting. In 2024, the stunting prevalence was recorded at 16.90%, and in 2025 the number of stunting cases increased by 18.63% compared with the previous year. This condition indicates that the implementation of the stunting intervention program has not yet been fully successful in reducing the prevalence of stunting. This study aimed to analyze the implementation of the First 1,000 Days of Life (1,000 HPK) Specific Nutrition Intervention Program for stunting management at the Sarwodadi Community Health Center. This study employed a descriptive qualitative design using a case study approach. Data were collected through in-depth interviews, observations, and document reviews. The data were analyzed using data reduction, data display, and conclusion drawing techniques. Data trustworthiness was ensured through source and method triangulation. The findings revealed that several indicators of the specific nutrition intervention program targeting the first 1,000 days of life had not been optimally achieved. In terms of input, there were limitations in human resources, and specialized training for community health volunteers (cadres) on stunting management had not been systematically planned. Regarding the process aspect, the frequency of direct field monitoring remained limited. In the output aspect, the coverage of exclusive breastfeeding, as well as iron supplementation (30 and 90 iron-folic acid tablets) for pregnant women, had not reached the established targets. The study recommends conducting regular monitoring and evaluation of the First 1,000 Days of Life nutrition intervention program to improve its effectiveness in preventing and reducing stunting.